(:unas) unassigned - Pussadee Tangwatcharin; Prapaporn Khopaibool (My University, 2012)
Lauric acid and monolaurin in combination with lactic acid were evaluated for their effectiveness in reducing total plate count (TPC) and Staphylococcus aureus of fresh pork loin.Fresh pork loins were dipped in control (non treated), sterile distilled water, 3.2 mg/ml lauric acid, 0.4% (v/v) lactic acid, 0.2 mg/ml lauric acid + 0.1% (v/v) lactic acid, 0.1 mg/ml monolaurin, 0.05 mg/ml monolaurin + 0.1% (v/v) lactic acid solution.Total plate count, population of S. aureus and physical and sensory qualities were determined.TPC and S. aureus counts found in pork loin treated with lauric acid and monolaurin alone and in combination with lactic acid were not significantly different (P > 0.05).The colour, odour and overall acceptability of the pork loins were adversely affected by the treatment with lactic acid alone, but when combinations of the agents were used the sensory quality was acceptable.Furthermore, during storage, both lipids in combination with lactic acid controlled growth of S. aureus for 8 and 4 days of storage at 4 and 15 °C respectively, and TPC for 8 and 2 days of storage at 4 and 15 °C, respectively.The low pH of the antimicrobials caused the highest weight loss of range 4.41-5.38%drip loss, 22.56-23.35%cooking loss, and discolouration.In contrast, L * , PV, TBARS of pork in all treatments increased but shear force and a * decreased as storage was longer in all solution types (P < 0.05).However, for sensory acceptability, there was no loss of colour or adverse odour and the overall acceptability scores remained satisfactory.
Keywords: null